Prednisolone in Dogs—Plasma Exposure and White Blood Cell Response - Ekstrand, Carl; Pettersson, Helena; Gehring, Ronette; Hedeland, Mikael; Adolfsson, Sara; Lilliehöök, Inger (Frontiers in Veterinary Science, 2021)
Glucocorticoids such as prednisolone are commonly used in dogs but there is sparse quantitative pharmacokinetic and pharmacodynamic information of this drug in this species. The objective of this study was to quantitatively characterize the concentration-effect relationship for prednisolone in dogs on neutrophil and lymphocyte trafficking and cortisol suppression. Nine beagles, 2–12 years old and part of a group for teaching/research were used in a 4-way crossover experiment including two treatments, active or placebo, administered either per os (PO) or intravenously (IV). Plasma was analyzed for prednisolone and cortisol using ultra-high performance liquid chromatography – tandem mass spectrometry. Leucocyte counts were performed in whole blood. Data was then analyzed by non-linear mixed effect modeling to estimate pharmacokinetic and pharmacodynamic parameters. After administration of prednisolone sodium succinate IV, the typical value (between subject variation) for total body prednisolone clearance was 1,370 ml/h·kg (13.4%). The volumes of the central and peripheral compartment were 2,300 ml/kg (10.7%) and 600 ml/kg (16.0%), respectively. The terminal plasma half-life was 1.7 h. The prednisolone plasma concentration producing 50% of the maximum response was 10 ng/mL (90.3%), 22.5 ng/ml (52.3%) and 0.04 ng/mL (197.3%) for neutrophil, lymphocyte and cortisol response, respectively. The administered dose (1 mg/kg) increased neutrophil and decreased lymphocyte numbers but not over the entire dosage interval of 24 h, due to the short half-life. However, glucocorticoids have a wide range of responses. An anti-inflammatory response due to altered gene transcription might have a longer duration. Future studies on the anti-inflammatory potency together with data presented are needed to optimize future dosage recommendations in dogs.